ANALISIS YURIDIS TERHADAP PUTUSAN HAKIM DALAM PERKARA NO.1144/PID.B/2017/PN.MKS PADA PELAKU TINDAK PIDANA PENGANIAYAAN YANG MEYEBABKAN KEMATIAN DALAM PELAKSANAAN ORIENTASI MAHASISWA BARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The Study Orientation Period Campus Introduction is one of the things that sounds horror among new students, it cannot be denied that its existence is not only found at the tertiary level, but at various levels of elementary schools such as junior high and high school. For example, in the case decision No.1144 / Pid.B / 2017 / PN.Mks, in that case the defendant was sentenced to only probation while the victim has died. Based on the rules issued by the Regulation of the Minister of Education and Culture (Permendikbud) Number 18 of 2016 concerning the Introduction of the School Environment for New Students listed in Article 5 paragraph (1) Sub (b) which states that it is prohibited to involve senior students (seniors) and / or alumni as organizers and sub (e) who state that the introduction of a school environment is prohibited from hazing or other acts of violence. But in reality there are still many cases of hazing committed by seniors to their juniors.The purpose of writing this thesis, namely; first, knowing the judge's decision and the judge's consideration in case No.1144 / Pid.B / 2017 / PN.Mks on the perpetrator of a criminal offense of torture that caused death in the implementation of new student orientation. This research method can be classified in the type of normative legal research or literature study, because the researcher conducts research on the legal synchronization level.From the results of the research conducted, it can be concluded that in the verdict, the judge has imposed a criminal offense against the perpetrator, taking into account several considerations, but only probation was imposed. Of course this is felt to be unfair because one of the purposes of punishment is to make people deterred from committing crimes and in making considerations, judges must pay attention to the values of justice for victims and perpetrators, because from these considerations will result in a decision that will be carried out. by the perpetrator in accordance with applicable legal provisions.Keywords: Judge's Decision-Crime - Persecution Leads to Death